Hardened material properties of self‐compacting concrete - Holschemacher, Klaus (Journal of Civil Engineering and Management, 2004)
Self‐compacting concrete (SCC) is an innovative construction material with a favourable rheological behaviour, which is caused by its modified concrete composition. Based on this fact SCC offers improved fresh concrete but also hardened material properties and therefore many advantages regarding the productivity and the design potential compared with normal vibrated concrete. Consequently, the amount of SCC, used for structural purposes has strongly increased worldwide in the last years. In this context it is necessary to know, if it is possible to apply the current design rules, eg Model Code 90 and Eurocode 2, that are based on years of experience on normal vibrated concrete, to structural members made of SCC as well. This paper represents the analysis of own and internationally published test results of the compressive strength, tensile strength, modulus of elasticity, bond behaviour and the time‐dependent deformations of SCC in comparison with conventional concrete, in order to give a general statement regarding the agreements and differences between the hardened material properties of these concretes.First Published Online: 14 Oct 2010